Maternal Thinking in Doris Lessing’s The Golden Notebook: An Analysis of Impossibility - Miloš, Brigita; Dulibić-Paljar, Dubravka (American & British Studies Annual, 2021)
The paper develops around the notion of motherhood in Doris Lessing’s seminal novel The Golden Notebook. Starting from the premise of Lessing’s persistent refusal of the label of feminist writer, but theoretically sustained through an elaboration of her stance on the novel’s readership, the main argument of the paper emphasises Lessing’s (semantic) accordance with the feminist motherhood theory of the early sixties. In addition, through the notion of motherhood, the article aims to provide an account respectful towards Lessing’s request for a complex and coherent reading of her work.